Didactic classroom studies A potential research direction - Osbeck , Christina; Ingerman, Åke; Claesson, Silwa (Kriterium, 2018)
"In the anthology Didactic classroom studies. A potential research direction didactic classroom studies are characterized and discussed in relation to, on the one hand, didactics and, on the other hand, classroom studies. It is argued that classroom studies has particular potential for realizing the ambitions that constitute didactics in empirical studies - to simultaneously focus processes of teaching and learning as well as the content of these processes and how they interact, and at the same time emphasize that teaching and learning as classroom work is intentional and flows towards specific goals. Classroom studies are not limited to pay (empirical) attention to the student, teacher or content, but have the capacity to focus on how these aspects interact and depend on each other. The research is delimited in contextual and situational terms of teaching-learning wholes, rather than primarily in terms of components (e.g., student, teacher or content). This translates to that classroom studies can capture and examine teaching and learning processes including their dependence of specific contexts in which they are conducted. The potential that lies in the work of classroom studies for didactics is attended to and described in more detail than previous research has done along with a set of example studies, which is a significant contribution of the anthology as a whole. The book gives examples of eight different classroom studies that focus different content areas with varied but related theoretical perspectives and specific methodological approaches. Through these concrete examples, as described and discussed in relation to each other in two concluding commentary chapter, the didactic value of the studies is made visible and didactic classroom studies are described as constituting 'a potential research direction'. Through a detailed analysis of the chapters with empirical studies - in terms of their research questions and knowledge interests, research contexts, theoretical and analytical perspectives, specific empirical designs and didactical consequences - a number of issues are identified that could be addressed and further developed. In this way, the volume contributes not only to identifying didactic classroom studies as a potentially central research focus in educational science but also outlines a further direction for this research."